SYSTEMATIC LITERATURE REVIEW: PENGARUH INTERAKSI SOSIAL DALAM KELOMPOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Nur Solehah, Rahma; Pujiastuti, Heni; Ihsanudin, Ihsanudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This systematic literature review investigates how peer interactions within group-based instructional settings affect the mathematical problem-solving competencies of junior high school learners. A literature search was executed via Google Scholar, combining the terms social interaction, group learning, mathematical problem solving, and junior high school students, with a temporal filter spanning 2015 to 2025. Applying the PRISMA screening protocol to the initial pool of 35 records yielded 14 empirical studies that satisfied the predefined inclusion criteria. Cross-study synthesis reveals that social dynamics embedded in cooperative and collaborative pedagogies consistently enhance students’ problem-solving proficiency. Key mechanisms driving this improvement include structured peer dialogue, reciprocal support, and collective self-regulation. Instructional frameworks such as STAD, Think-Pair-Share, Jigsaw, and Peer-Assisted Learning demonstrate strong efficacy, particularly when implemented in academically diverse groups. The effectiveness of these approaches is further moderated by learners’ foundational knowledge and the presence of socially mediated regulatory scaffolds. These findings offer actionable insights for middle school mathematics educators seeking to harness group-based social dynamics to elevate students’ analytical and problem-solving performance.